Propuesta de intervención psicoeducativa para prevenir el acoso escolar en los estudiantes de séptimo año de la escuela de educación básica Mons. Juan María Riofrío, periodo 2018-2019. - Poma Jimenez, Michelle Anahi (2019)
Bullying is a behavioral and emotional problem that affects the interaction between classmates causing deterioration in the school environment that is why in this thesis entitled: PROPOSAL FOR PSYCHOEDUCATIONAL INTERVENTION TO PREVENT SCHOOL HARASSMENT IN SEVENTH GRADE STUDENTS OF THE BASIC EDUCATION SCHOOL MONS. JUAN MARÍA RIOFRÍO, PERIOD 2018-2019., It was raised as a general objective: Develop a psychoeducational intervention proposal to prevent bullying in seventh grade students of the basic education school Mons. Juan María Riofrío, period 2018-2019. The research responded to a descriptive, crosssectional approach and a pre-experimental design, the methods used were: scientific method, analytical-synthetic, deductive-inductive and as an instrument the Cisneros Self-test, to identify the overall rate and intensity of bullying, as well as the characteristics of it. The sample under study corresponds to 30 students chosen by nonprobabilistic sampling. The most significant pre-test results are found in the intensity of harassment and in the areas of restriction-communication, intimidation-threats, social exclusion-blocking and robberies. After the application of the proposal, it was verified through the post-test that said levels were markedly reduced, placing the highest frequency in the medium and low levels, being the most significant scores in the intensity of school bullying and in the areas of communication-restriction, exclusion-social blockade and robberies. Regarding the effectiveness of the activities carried out, it was 91.88% validating the proposal, Therefore, it is recommended that the educational institution implement permanent activities that aim to prevent bullying.